Heterogeneous expectations, optimal monetary policy and the merit of policy inertia - Gasteiger, E. (Journal of Money, Credit and Banking, 2014)
The design and analysis of optimal monetary policy is usually guided by the paradigm of homogeneous rational expectations. Instead, we examine the dynamic consequences of design and implementation strategies, when the actual economy features expectational heterogeneity. Agents have either rational or adaptive expectations. Consequently, the central bank's ability to achieve price stability under heterogeneous expectations depends on its objective and implementation strategy. An expectations-based reaction function, which appropriately conditions on private sector expectations, performs exceptionally well. However, once the objective introduces policy inertia, popular strategies have similar determinacy properties, but they are less operational. This finding calls for new implementation strategies under interest rate stabilization.